Can Ali Pass the Program? An Empirical Study of a Blind ICT Student challenges at Arab Open University - AlSoufi, Ali (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
We live in visually oriented society, in which the computer is becoming as commonplace and integral part of every student’s educational experience. It plays essential role in transforming the way in which postsecondary programs educate and communicate with their students. Faculty is encouraged, often strongly, to incorporate more computer technology and web-enhanced components in their courses as well as to develop distance education courses and programs. Recently many textbooks include CDs that contain additional course material, course assignments, animated visual aids and tests to support both faculty and the students. Students usually use their computers to write papers, register a course and communicate with faculty and other students. These actions constitute challenges for students that are visually impaired or blind. People with disabilities are often misunderstood and discriminated against when it comes to education and especially when they pursue their higher education. The purpose of study is to explore challenges with respect to the course materials used in the first degree in IT at Arab Open University. To achieve this a blind student, who is the first experience at the university, is used as a case through studying his background and monitoring his progress in the first year of study, while a comprehensive analysis on the course material, that he will be covering in the 4 years of the program, was conducted to predict whether he will able to complete his studies successfully in the IT program. Furthermore the challenges explored would be used to enhance the program delivery for visually impaired students.